A 70‐Year‐Old Mystery in Technetium Chemistry Explained by the New Technetium Polyoxometalate [H7O3]4[Tc20O68] ⋅ 4H2O. Issue 54 (4th August 2021) - German, Konstantin E.; Fedoseev, Alexander M.; Grigoriev, Mikhail S.; Kirakosyan, Gayane A.; Dumas, Thomas; Den Auwer, Christophe; Moisy, Philippe; Lawler, Keith V.; Forster, Paul M.; Poineau, Frederic
Abstract: [H7 O3 ]4 [Tc20 O68 ] ⋅ 4H2 O [1 ] was prepared from an aqueous Tc2 O7 solution concentrated over anhydrous H2 SO4 . [Tc20 O68 ] 4− is the first polyanionic species to be reported for Tc. The unit cell contains one centrosymmetric [Tc20 O68 ] 4− polyanion as well as hydronium ions and water molecules. The core of the structure consists of four Tc(V)O6 octahedra that form a square Tc4 O4 ring. The four Tc(V)O6 octahedra are decorated by sixteen Tc(VII)O4 tetrahedra. Calculations show the bonding within the Tc4 O4 ring to consist of a 3‐center bond formed between each neighboring pair of Tc atoms and their bridging oxygen. Calculations also indicate that a strong d → d electronic transition at 513 nm is the origin of the red color of [1 ]. The characterization of red HTcO4 solutions by X‐ray absorption spectroscopy has complemented the description of this compound in aqueous solution. The formation mechanisms in solution, including the possible role of technetium's radioactivity in the formation of [1 ], are discussed. Abstract : The red product obtained upon concentration of an HTcO4 solution contains the [Tc20 O68 ] 4− polyanion, which is the first technetium polyanionic species reported. The [Tc20 O68 ] 4− species exhibits a molecular structure never observed before and consists of a square‐planar Tc4 O4 ring decorated by sixteen Tc(VII)O4 units. The red color is due to d→d electronic transitions between the Tc(V) atoms of the central ring.